Ophthalmic Manifestations and Genetics of the Polyglutamine Autosomal Dominant Spinocerebellar Ataxias: A Review - Park, Jun Young; Joo, Kwangsic; Woo, Se Joon (Frontiers in Neuroscience, 2020)
Spinocerebellar ataxia (SCA) is a part of the cerebellar neurodegenerative disease group that is diverse in genetics and phenotypes. It usually shows autosomal dominant inheritance. SCAs, always together with the cerebellar degeneration, may exhibit clinical deficits in brainstem or eye, especially retina or optic nerve. Interestingly, autosomal dominant SCAs share a common genetic mechanism; the length of the glutamine chain is abnormally expanded due to the increase in the cytosine–adenine–guanine (CAG) repeats of the disease causing gene. Studies have suggested that the mutant ataxin induces alteration of protein conformation and abnormal aggregation resulting in nuclear inclusions, and causes cellular loss of photoreceptors through a toxic effect. As a result, these pathologic changes induce a downregulation of genes involved in the phototransduction, development, and differentiation of photoreceptors such as CRX, one of the photoreceptor transcription factors. However, the exact mechanism of neuronal degeneration by mutant ataxin restricted to only certain type of neuronal cell including cerebellar Purkinje neurons and photoreceptor is still unclear. The most common SCAs are types 1, 2, 3, 6, 7, and 17 which contain about 80% of autosomal dominant SCA cases. Various aspects of eye movement abnormalities are evident depending on the degree of cerebellar and brainstem degeneration in SCAs. In addition, certain types of SCAs such as SCA7 are characterized by both cerebellar ataxia and visual loss mainly due to retinal degeneration. The severity of the retinopathy can vary from occult macular photoreceptor disruption to extensive retinal atrophy and is correlated with the number of CAG repeats. The value of using optical coherence tomography in conjunction with electrodiagnostic and genetic testing is emphasized as the combination of these tests can provide critical information regarding the etiology, morphological evaluation, and functional significances. Therefore, ophthalmologists need to recognize and differentiate SCAs in order to properly diagnose and evaluate the disease. In this review, we have described and discussed SCAs showing ophthalmic abnormalities with particular attention to their ophthalmic features, neurodegenerative mechanisms, genetics, and future perspectives.